Project portfolio management implementation pitfalls - A. Leonard; A. Swanepoel (South African Journal of Business Management, 2010)
Project portfolio management could be regarded as one of the most comprehensive ways of managing a software project environment. To implement such a management approach in a large organisation, could also be seen as an endeavour that can only have a chance of success if all role players understand the pitfalls involved and how to deal with each. In this paper, a structured approach is proposed to identifying and addressing pitfalls that may potentially hinder the successful implementation of project portfolio management as a strategic initiative in an organisation. Furthermore, the paper presents an approach to combine checklists and pitfall management theories to identify those pitfalls that may realise during the implementation of project portfolio management.
Keywords: 650